Analysis of Determinants of Personal Taxpayer Compliance on Income Tax Revenue in Malang City - Syafriel, Muhammad; Roziq, Mohammad (Program Studi Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2025)
This study aims to evaluate the implementation of revenue and expense recognition based on PSAK 72 in a construction service company. The object of this research is PT X, which manageslong-term construction projects with contracts worth billions of rupiah. The approach used is descriptive qualitative with a case study method. Data were collected through interviews, observations, and documentation. The results of the study indicate that the company has partially implemented the principles of PSAK 72, particularly in the aspects of contract identification and transaction price determination. However, the revenue recognition method used—the completed contract method—has not fully aligned with the percentage-of- completion approach as stipulated in PSAK 72. Furthermore, the classification and recording of expenses have not entirely reflected the matching principle between revenue and expenses. This study suggests that the company strengthen its accounting information system and conduct regular training for financial personnel so that the implementation of PSAK 72 can be applied optimally and accurately.